Power and Partnership (Book collections on Project MUSE., 2014)
The purposes of this book are to focus on faith-based development with a particular emphasis on the question of power, to deal with the dark sides and the positive sides of power and partnership and how the two interact, to present relevant case studies on the topic from some of the world religions, and to publish new material and insights on the interdisciplinary debate on the topic. The book thus aims to fill a vacuum in the general discourse on faith-based development.